3b+6b=63

Simple and best practice solution for 3b+6b=63 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3b+6b=63 equation:


Simplifying
3b + 6b = 63

Combine like terms: 3b + 6b = 9b
9b = 63

Solving
9b = 63

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Divide each side by '9'.
b = 7

Simplifying
b = 7

See similar equations:

| h=100-16t^2 | | -4p-(1-6p)=0 | | 0.68=0.17+1.7k | | 3(4m-7)= | | 36-6y=8x-5x+21 | | 5r^2-50r+120= | | .4(4x+2)=3(1-2x)+13 | | 4x+4.3=4.9 | | 14+3-y+6y=27 | | 192/96/93= | | 3w-15= | | -5(x-5)-2x=7-7(x+2) | | 8y-5y+21=36-6x | | 15a^2+32a-7=0 | | (7x+14-3x+2y)(14x-7+12x-2y)= | | (3-x)*5.7=18 | | 30-25=48 | | -(2k-6)=5(1+8k)+5 | | 8y-5y+21=36-6y | | -40=-5x+x-4 | | 0.3x-0.2(17-5x)=-0.6(x-7) | | -3x+12+5x=14 | | 4a-3(a-2)=(3a-2) | | 7(5x-3)+9=58 | | 4m-6m=4 | | 7u-(10-3u)=5(3u+4) | | (2x+3)+(4x-1)= | | -9x-5-8-x= | | 11-4x=3+6y | | x-2x+3x=1000 | | p/2-9=-1 | | 0.2x-0.8(8-5x)=0.5(x-6) |

Equations solver categories